Perancangan Boardgame dalam Upaya Mengenalkan Anak Usia 10 – 12 Tahun Terhadap Cerita Rakyat “Putri Ayu” - Marcellino Aditya; Koni Herawati; Danella Patricia (Penerbit Itenas, 2025)
Folklore is one of the cultural traditions passed down from generation to generation. The great diversity of folklore in circulation is one proof of the many cultures that exist in Indonesia. Despite having many folktales, not all of them are known by the community and children. This is also due to the decline in people's interest in Indonesian folklore from generation to generation. The availability of media or facilities that are less suitable for children makes them less interested in folklore. Instead of folklore, children prefer books by original authors or the imagination of authors and stories from abroad that are more modern. Introducing folklore to early childhood and elementary school needs to be done with fun activities, this needs to be done in order to attract children's attention to participate. This research aims to develop board game media as a new form of introduction to children, so that they become interested in recognizing a folklore. This development is designed using the SCAMPER design method, through this method it can help the product design process in developing original ideas for the product. Where the board game is designed as an entertainment game so that children can play it at any time.